El rol de la comunicación en las instituciones del estado: del valor reputacional a la legitimidad en la provisión de servicios públicos - Torres Castro, Daniel Eduardo (2024)
In the corporate world, communication is considered, internally, as “central nervous system and the vital flow”; and outside the company, as “social being”; in general, as one of its four cardinal points (with identity, culture, and image). In the public sector, communication has been gaining its own space, through directorates or offices of communication and institutional image, as managing offices, leaving behind the traditional press offices dedicated to issuing statements and attending to interviews with shift holders in crisis situations. The strategic management of communication in government offices allows not only the construction of an identity and reputational value, but also to consolidate the legitimacy that every public institution requires for the provision of its services to citizens. This report gives an account of the work experience of Daniel Torres, a bachelor’s in communications from Universidad de Lima since 2001, and presents those works and communication products with which he contributed to improving the brand identity of the institutions (mainly governmental) where he has worked, and to strengthen their reputation by seeking to be recognized as leaders in their sector.